Vor-Sicht im Straßenverkehr - Experimentelle Untersuchung der somatischen Antizipation von Risiko - Heine, Tobias (Karlsruher Forschungsberichte zur Arbeitswissenschaft und Betriebsorganisation / Institut für Arbeitswissenschaft und Betriebsorganisation (ifab), Karlsruher Institut für Technologie, 2018)
Based on the Somatic Marker Hypothesis, an attempt is made to measure the anticipation of risky traffic situations by means of the electrodermal activity. The results indicate that the strength of the anticipatory electrodermal activity is systematically related to situational factors of a traffic situation. In addition, a model was derived that postulates an inverted U-shaped relationship between driver's experience and anticipatory electrodermal activity.